AI Empowerment and Decision Intelligence: A Business Analytics Approach to Gen Z-Led SMEs - Zerine , Ismoth; Islam, Md Mainul; Doha, Md Zulkernain; Biswas , Younis Ali (Electronic Journal of Business and Management, 2026)
The purpose of this study is to examine factors affecting decision making performance in the field of AI and technology adoption among Gen Z-led small and medium enterprises (SMEs). A cross-sectional, quantitative study aligned with the positivist paradigm and hypothetical-deductive reasoning. A sample of 286 respondents were selected using a stratified random sampling method. It was collected through structured questionnaires on study variables and analysed using Python Matplotlib and SPSS v25 through hierarchical multiple regression. The results show that all five hypotheses are significantly and positively associated with decision-making performance, and the largest standardized coefficient is for entrepreneurial flexibility. These results emphasise the need for both technological readiness and entrepreneurial characteristics to improve decision making in Gen Z SMEs. The present study adds to the emerging body of knowledge on digital entrepreneurship by combining insights from the behavioural and technological perspective. The study stands out because of its emphasis on the Gen Z entrepreneurs operating in an SME sector characterized by high digital penetration and innovation and is based on how the adoption of AI influences strategic decision-making. We incorporated California-specific responsible AI considerations like CCPA compliance along with transparency and explainability.